PENERAPAN MODEL PEMBELAJARAN KOOPERATIF THINK PAIR SHARE (TPS) UNTUK MENINGKATKAN PRESTASI SISWA PADA POKOK BAHASAN LARUTAN PENYANGGA DIKELAS XI IPA SMA NEGERI 1 SUNGAI APIT - ', Suryana; M.Noer, Asmadi; ', Susilawati (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2017)
Abstract: This research aims to increase student achievementon the Buffer topic at class XI SMAN 1Sungai Apit. The research is experiment research with pretest-posttest design. The samples of research were the students of class XI 2 as the experimental class and students of class XI 3 as the control class. Experimental class is a class that is used the cooperative learning model think pair share (TPS) while the control class was not. Data analysis technique used is t-test. Based on analysis of data obtained that tarithmetic> ttable is 2,70 > 2,00, means that the use of cooperative learning model think pair share (TPS) can improve student achievement on of buffer solution topic the learning increase resect about of 10,56%.Keywords : Learning Achievement, Cooperative Learning Model Think Pair Share (TPS), and Buffer Solution